Indonesia-Malaysia relations : cultural heritage, politics and labour migration - Clark, Marshall Alexander; Pietsch, Juliet (New York : Routledge, 2014)
'Examines the international relations of Southeast Asia, focusing on how these are affected by the special Indonesia-Malaysia bilateral relationship - Malaysia and Indonesia, although separate states, can be seen as constituting a single Indo-Malay cultural world'--
Uneasy neighbours -- Language and mythology -- Cultural contestations -- Museums -- Islam -- Ethnicity -- Citizenship -- Regionalism -- Democracy.
Includes bibliographical references (page 213-231) and index.
Keywords: Indonesia -- Relations -- Malaysia; Malaysia -- Relations -- Indonesia; Malay Archipelago -- Civilization